A mulher sábia e a sabedoria mulher símbolos de co-inspiração Um estudo sobre a mulher em textos de Provérbios - Lopes, Mercedes (2007)
In the book of Proverbs, specifically in chapter 1 verses 20-23 and chapters 8 and 9, it is possible to perceive references that lead us to identify a symbol which has been called the wisdom-woman, or wise-woman. Its interpretation has a long and polemic history. While analyzing the textual links between these verses and the poem of Proverbs 31, it is possible to realize that the symbol related to the wisdom of a woman seems to be taken from the daily life of a person that, with great audacity, participates in the process of building history and human relationships in the context of that moment (the post-exilic period), in Judah. These links and texts emphasize the great value of the woman and her proximity to God. She is presented as the one who has the power of offering (Pr 8,35; 9,6) and preserving life (Pr 31), the one capable of experiencing and transmitting the ethical values that are fundamental to every day family relationships (Pr 1,8; 6,20; 31,2-9.26). This symbol also represents the memory of the ancient cults that were celebrated in private homes to commemorate and guarantee on-going life. Even the memory of different goddess were present in these rituals, in that they were not opposed to the rituals dedicated to Yahveh. It is possible to state this because in the inner dynamic of the celebrations thattook place in those homes these divinities (goddess-Yahveh) were worshiped. These texts show a change in the way of understanding the role of the woman in her context. This new understanding appeared during the period of captivity, when there was neither sanctuary nor government to provide adequate organization for the people in their struggle for liberation. In this case, homes became substitutes for sanctuaries and women were empowered, even in the midst of a patriarchal society. The wisdom of the women is manifested in the home space, emphasizing relationships of inclusion and solidarity during the period of the second temple, a time in which various laws related to impurity were significant.(AU)